Proof that it is not always optimal to locate bonds in a tax-deferred account - Marcel Marekwica; Raimond H. Maurer (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2006)
The tax codes in many countries allow for special tax advantages for investments in special retirement plans. Probably the most important advantage to these plans is that profits usually remain untaxed. This paper deals with the question, which assets are preferable in a taxdeferred account (TDA). Contrary to the conventional wisdom that one should prefer bonds in the TDA, it is shown that especially in early years, stocks can be the preferred asset to hold in the TDA for an investor maximizing final wealth, given a certain asset allocation. The higher the performance of stocks compared to bonds, the higher the tax burden put on stocks compared to bonds. Simultaneously, the longer the remaining investment horizon, the larger the relative outperformance of the optimal asset location strategy compared to the myopic strategy of locating bonds in the TDA. An algorithm is provided to determine the investment strategy that maximizes (expected) funds at the end of a given investment horizon when there is an analytical solution.
Keywords: 330